Perceptions of selected Filipino gamers on the clothing designs of Filipino characters in foreign video games - Peñaflor, Cheena Pamela T.; Msristela, Candy Mae (Quezon City University of the Philippines Diliman, 2024)
The globalization of the gaming industry has propelled the inclusion of Filipino characters in foreign video games to increase cultural representation. This market development strategy is geared towards cultivating continuous engagement from the Filipino player base. In line with this ongoing trend, the study analyzed the perceptions of selected Filipino gamers toward the representation of these characters through their clothing designs. The study purposively sampled seven (7) BS Clothing Technology students who met the inclusion criteria of having played either Mobile Legends: Bang Bang or Valorant, two of the largest foreign video games in the Philippines that have introduced Filipino characters. The study utilized a combination of semiotic and thematic analysis and conducted personal interviews structured into three parts: pre-evaluation, character evaluation, and post-evaluation. The study shows that the clothing designs of the characters can be considered signifiers of the Filipino identity, in terms of their contingent links to aspects of Filipino culture, as described by primary and secondary visual and verbal references, alongside the Filipinos’ lived experiences at present. However, the meanings associated with the non-signifiers in each character, which point to dilution, Westernization, censorship, and exoticization, should be addressed for the creation of future character clothing designs and Filipino characters in all types of foreign media.
In partial fulfillment for the Degree of Bachelor of Science in Clothing Technology
Thesis
Keywords: Video game characters -- design; Video game characters; Cultural representation; Filipino characters